Laparoscopic distal pancreatectomy in patients with poor physical status. Issue 6 (June 2021) - Sahakyan, Mushegh A.; Tholfsen, Tore; Kleive, Dyre; Waage, Anne; Buanes, Trond; Labori, Knut J.; Røsok, Bård I.; Edwin, Bjørn
Abstract: Background: Laparoscopic distal pancreatectomy (LDP) is advantageous over open surgery in the treatment of benign pancreatic lesions and low-grade malignancies. Yet the evidence on the relationship between comorbidities and the outcomes of LDP remains scarce. Methods: Patients who had undergone LDP for all indications between April 1997 and December 2019 were included. Preoperative physical status was defined according to the American Society of Anesthesiology (ASA) criteria. Perioperative outcomes were compared between the patients with high (ASA III–IV) and low/moderate anesthetic risk (ASA I–II). Results: A total of 605 patients were eligible for analysis including 190 with ASA III–IV and 415 with ASA I–II. The former was associated with older age, male gender, preexisting medical conditions, greater total number of comorbidities and red blood cell transfusion. The rate of medical complications was significantly higher in high-risk patients. Multivariable analysis identified ASA III–IV and operative time as independent predictors for medical complications. Overall/severe morbidity, surgical complications and mortality rates were similar. Conclusions: Poor physical status defined as ASA grades III–IV predicts medical complications, but has a limited impact on surgical complications and severe morbidity of LDP. Thus, it should not be considered as a contraindication for LDP.